BODIES OF KNOWLEDGE;BODIES OF KNOWLEDGE (AFRICAN SUN MEDIA, 2021)
Spanning the countries of South Africa, Swaziland, and Ghana, this collection of work brings into focus child and youth experience together as a collage of anthropology, creative writing, poetry, and the fine arts.
Keywords: Terminally ill children -- Africa -- Personal narratives.; Abused children -- Africa -- Personal narratives.; Phenomenology.; Well-being -- Health aspects -- Africa.; Well-being -- Africa -- Religious aspects.; Enfants malades en phase terminale -- Afrique -- Récits personnels.; Phénoménologie.; Bien-être -- Afrique -- Aspect religieux.; phenomenology.; Abused children; Phenomenology; Terminally ill children; Well-being -- Religious aspects; Africa; Personal narratives